Construção de um instrumento de avaliação do autocuidado dos pacientes com diabetes Mellitus tipo 2 - Mendonça, Simonize Cunha Barreto de (2016)
This is a methodological development study with psychometric approach, which aims to build an assessment tool of self-care of patients with diabetes mellitus type 2 (DM2). The methodological path was guided by theoretical processing procedures of psychometric instruments and the theoretical foundation for self-care model of Dorothea Orem was used. Theoretical procedures included the definition of the construct "Self-care of patients with DM2" and was conducted with the use of the theoretical framework adopted; it gives related and qualitative study literature, with the focus group technique, using content analysis. Three different focus groups, one of eight health professionals with experience in the management of patients with DM2 and the other two compounds in 26 patients with DM treated in an educational program of a health service outpatient formed in the State Sergipe. This study allowed us to describe the meanings attributed by professionals and patients to self-care six requirements in the diversion of Health according to the theory of Orem, which were defined as the theoretical dimensions of the instrument. We requirements were: finding and securing adequate multidisciplinary care (mutual accountability, accessibility, basic conditioning factors); know and consider the disease and its complications (disease-related aspects); adhere to treatment (drug treatment and drug); know and consider the inconvenience of treatment (side effects and psycho-emotional distress); accept the disease (humanization of treatment, recognizing the need to control the disease, recovery team Health and treatment outcomes), and learn to live with the effects of the disease (enhancement of style and self-esteem). It was developed an assessment tool Self-care of patients with DM2 (INAAP-DM2) containing 131 itens and consists of a Likert scale of five points and to measure in each of the dimensions the requirements of self, classifying three levels: Totally Compensatory, Partially Compensatory and education support. The same was subjected to a validation process content. For this, the instrument passes through a semantic and conceptual analysis by a panel of seven judges. It was subsequently conducted a pre-test with 14 patients with DM2. For content validation, the judges evaluated items related to the domains to which they belonged, their stay in the instrument and presents psychometric criteria. It was calculated the content validity index for each items (IVCi) and mean IVCi (IVCS) for all the items of each domain. The content validity of the instrument was considered excellent when it came to a IVCi ≥ 0.75 and an average of IVCS ≥ 0.90. After calculation was obtained those 129 items were IVCi ≥ 0.78 and all domains showed IVCS ≥ 0.90. With regard to remain in the instrument, all items showed IVCi ≥ 0.78 and the set of items for each domain presented IVCS ≥ 0.90, that is, the domain A (0.99) B (1.00) C (0, 98) D (1.00) E (0.97) and F (0,96). In the trial of psychometric criteria (objectivity, clarity, precision, criminality, simplicity, relevance and credibility mode), in general, they showed a satisfactory assessment items, and have been updated according to the suggestions of the panel of judges. The development of a technology that takes into account the multidimensional nature of this disease can help multidisciplinary teams in the use of a model of comprehensive care of patients with DM2.